Crisis Management as a Researach Province of Security Science - Skrabacz, Aleksandra; Pajka, Aneta; Więckowski, Bartłomiej (Roczniki Nauk Społecznych, 2024)
The issue of crisis management is constantly present in the literature, especially internationally. In Poland, researchers’ interest in this problem is relatively short-lived, as the concept itself stems from American solutions and was transferred to civil protection in the late 1990s. The aim of the article is therefore to present a structured overview of research on crisis management from 1945 through 2023, using bibliometric analysis. The origin of crisis management in Poland is discussed along with a bibliometric analysis of publications stored in the SCOPUS database.